2010
DOI: 10.12968/ijtr.2010.17.5.47843
|View full text |Cite
|
Sign up to set email alerts
|

Comparing stabilization training with balance training in recreationally active individuals

Abstract: Aims The present study was undertaken to compare the efficacy of lumbar core stability training with that of balance training, at improving the balance performance in the recreationally active individuals. Most of the studies to date have been conducted on sporting professionals, whose activity demands are higher than the norm. The present study focuses on the recreationally active population, for which the activity demands are comparatively lesser. Methods Thirty recreationally active subjects (15 males and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…Improvements in balance have been reported in various populations following a 6e8 week training program incorporating the Swiss Ball (Sekendiz et al, 2010), uniaxial or multiaxial unstable surfaces (Eisen et al, 2010), resistance training incorporating unstable surfaces (Sparkes and Behm, 2010;Schilling et al, 2009), core stability (Aggarwal et al, 2010) and progressive neuromuscular training (Filipa et al, 2010). The present results extend the past literature demonstrating the ability of a short, four-week targeted training program to increase balance in middle aged women (as documented by reduced positional errors during the BESS) through the manipulation of training variables that included base of support, stability, vision, resistance and torque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in balance have been reported in various populations following a 6e8 week training program incorporating the Swiss Ball (Sekendiz et al, 2010), uniaxial or multiaxial unstable surfaces (Eisen et al, 2010), resistance training incorporating unstable surfaces (Sparkes and Behm, 2010;Schilling et al, 2009), core stability (Aggarwal et al, 2010) and progressive neuromuscular training (Filipa et al, 2010). The present results extend the past literature demonstrating the ability of a short, four-week targeted training program to increase balance in middle aged women (as documented by reduced positional errors during the BESS) through the manipulation of training variables that included base of support, stability, vision, resistance and torque.…”
Section: Discussionmentioning
confidence: 99%
“…Training on unstable surfaces, exposing individuals to altered sensory input, is reported to increase muscular stress (Anderson et al, 2013) and may lead to gains in stability, proprioceptor activity, sway control, and improved core stability through neuro-adaptive mechanisms (Aggarwal et al, 2010;Schilling et al, 2009;McNeill, 2010). Anderson et al (2013) recently demonstrated that as the level of instability increased during a push-up protocol, there was a greater amount of muscle activation for the core stabilizers, prime movers and lower body stabilizers.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Similarly, Aggarwal and colleagues compared results from core stability and balance training protocols and found that both improved balance as measured by the stork balance test (a measure of static balance) and star excursion balance test (SEBT, a measure of dynamic balance), but neither improved functional balance as measured by a multiple single leg hop test. [7] In a 2010 study, Filipa and associates also used the SEBT as an outcome to measure the effects of 8 weeks of targeted neuromuscular and core stability, and found a 103% increase in composite score after finishing the programme. [14] …”
Section: Discussionmentioning
confidence: 99%
“…Only two studies of this population involved a targeted intervention [7,22] and seven of the 11 studies reported a significant improvement in a general performance measure. [19,20,24,2628,31] While beyond the scope of this review, core stability has also been implicated in prevention of athletic injury, [35,30] a concept that is tightly intertwined with performance.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6,14,18,24,35,38 The SEBT has also been used in healthy, recreationally active individuals over the age of 30 years. 5,21,44 Women over 40 years have greater instability and decreased joint position sense, thus justifying the screening of women for balance deficits before the age of 60 years to minimize fall risks.…”
Section: Discussionmentioning
confidence: 99%